Four new species of free-living marine nematodes of the family Desmodoridae (Nematoda: Desmodorida) and a redescription of Desmodora nini (Inglis, 1963) from the continental shelf off northeastern Brazil - Larrazábal-Filho, Alexandre L.; Silva, Maria Cristina Da; Esteves, André M. (Zootaxa, 2015)
Four new species of marine nematodes were collected from the continental shelf of the Potiguar Basin in northeastern Brazil. Zalonema vicentei sp. n. and Zalonema mariae sp. n. are characterized by having multispiral fovea amphidialis, lateral alae and ventral ala. These features also are found in Pseudochromadora, Desmodorella and Psammonema. They differ in the cephalic arrangement, and shape of the cephalic capsule and the fovea amphidialis. Croconema fortis sp. n. resembles Desmodora in the shape of the fovea amphidialis and cephalic capsule, but differs in the number of subcephalic setae and ornamentation on the cuticule. Desmodora paraconica sp. n. is characterized by the loop-shaped fovea amphidialis and the long conical-cylindrical tail. This species is similar to the genus Bolbonema, but differs in having the cephalic setae anterior to the fovea amphidialis. Desmodora nini is redescribed, to record details lacking in the original description.